PROGRESSIVE COLLAPSE ANALYSIS OF SUSPENSION BRIDGE - Fantovi Muaja, Frianto
Progressive collapse has been a concern since the tragic collapse of the World Trade Center building on September 11, 2001. The Mahakam II Bridge is a clear example of a progressive collapse of a bridge, where one of the connecting elements in the midspan area of the bridge failed, causing the entire bridge to collapse. In this study, an analysis was carried out to determine the progressive failure of a three-span suspension bridge. A total of three bridge models were modeled, each with differences in frame element type, load application, failure assumptions, and hanger removal scenarios. The trigger for failure in the scenario of the bridge occurs because of the loss of the hanger in the middle of the span. The increase in force on other hangers was reviewed, and hanger failure was determined by the capacity of the clamp elements. From the results of the analysis of the capacity of the clamp element, it is found that the capacity of the clamp element is large enough so that the failure limit on the hanger does not use the entire capacity of the clamp element. The resulting analysis was for a bridge model where the bridge was modeled as truss elements, and when multiple hangers and frame elements failed, the bridge became unstable. For the bridge frame which is modeled as a beam element presuming there is no failure on the bridge frame, failure of the back hanger of the bridge will be achieved if enough of the front hanger is removed. For bridge frame modeled as truss and beam elements with the assumption that there is no failure on the frame, failure of the bridge hanger element occurs from the middle of the span in succession to the bridge pylon area.